The Role of Mother Personality Traits and Mind-mindedness as Mediators of Mother Attachment Toward Child Attachment - Yuspendi (Faculty of Psychology, Universitas Surabaya, 2013)
The objective of this study was to investigate the role of mother personality trait and mind- mindedness as mediators of mother attachment toward child attachment. The low correlation between mother attachment pattern and child attachment through a sensitivity mediator, support the search of other factors which could be a mediator of mother attachment towards child attachment. The samples (N =211) were housewives 25-45 year old as main caregivers with children of 3-5 year old residing in Bandung city. Instruments applied were Experiences in Close Relationship–Adult Attachment Questionnaire, Attachment Q-Set, Big Five Inventory, Mind-Mindedness and demographic data. Based on a structural equation model it was revealed that there was a fit between the theoretical model and the research data of mother attachment influencing child attachment mediated by mother trait extraversion, trait neuroticism, and mind-mindedness. It meant that mother personality and mind-mindedness played a role as mediators of mother attachment to child attachment Penelitian ini bertujuan untuk meneliti peran sifat kepribadian dan mind-mindedness ibu sebagai mediator kelekatan ibu terhadap kelekatan anak. Rendahnya hubungan pola kelekatan ibu terhadap kelekatan anak melalui mediator sensitivitas mendorong pencarian factor lain sebagai mediator. Sampel penelitian adalah ibu rumah tangga berusia 25 – 45 tahun sebagai pengasuh utama dan memiliki anak usia 3 – 5 tahun. Sampel (N = 211) adalah para ibu yang bertempat tinggal di kota Bandung. Alat ukur yang digunakan Experiences in Close Relationship–Adult Attachment Questionnaire, Attachment Q-Set, Big Five Inventory, Mind-Mindedness, serta data demografik. Berdasarkan model persamaan struktural diketahui ada kesesuaian (fit) antara model teoretik dan data penelitian yaitu kelekatan ibu memengaruhi kelekatan anak dengan dimediasi sifat extraversion, sifat neuroticism dan mind-mindedness ibu. Hal ini berarti sifat kepribadian dan mind-mindedness ibu berperan sebagai mediator kelekatan ibu terhadap kelekatan anak.